Composite electrode materials, preparation methods and their applications in transparent supercapacitors
Patent Information
- Application Number
- CN202511089389.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2045-08-05
AI Technical Summary
[0003]MnO2因其本身较高的比表面积和多孔结构有利于离子的快速扩散和表面反应,从而具有较高的储能性能,但其较差的导电性和低透明度也限制了其在透明超级电容器领域中的发展
(1)本发明提出的Ti3C2Tx-MXene/PEDOT:PSS/MnO2复合材料,MnO2这种赝电容材料可通过材料表面及近表面的快速可逆氧化还原反应储能,因此具有较高的比电容。但由于其本身本征载流子(电子或空穴)浓度较低,晶体结构中缺乏连续的电子传输通道,因此存在导电性能差的问题。其中Ti3C2Tx-MXene作为新型二维片层碳化物,本身具有较高的导电性和稳定性,而导电聚合物PEDOT:PSS的引入减少了MXene片的堆积,为离子传输和扩散提供了有效途径,故将Ti3C2Tx-MXene/PEDOT:PSS与MnO2复合,可以使复合材料表面形成稳定的导电通道,从而增强材料的导电性。
Smart Images

Figure CN120878470B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode materials technology, specifically to a composite electrode material, its preparation method, and its application in transparent supercapacitors. Background Technology
[0002] Transparent supercapacitors (TSCs) are a crucial component in the field of smart optoelectronic devices. Supercapacitors possess advantages such as high power density, rapid charge / discharge capabilities, and long cycle life. Most importantly, their unique energy storage mechanism makes them safer and more reliable than traditional lithium-ion batteries. TSCs, developed based on these advantages, not only inherit many of the strengths of traditional supercapacitors but also achieve a perfect combination of transparency and energy storage through structural design and material innovation, enabling better integration into transparent electronic devices. Despite the numerous advantages of TSCs, their commercialization still faces some challenges. S In the pursuit of high performance, the interrelationship between areal capacitance, electronic conductivity, and optical transmittance has become a key scientific problem limiting its development. Therefore, it is urgent to conduct research on designing and controlling material composition and constructing multi-level micro- and nano-structures to develop electrode materials with high transparency and energy storage performance.
[0003] MnO2 has high energy storage performance due to its high specific surface area and porous structure, which facilitates rapid ion diffusion and surface reactions. However, its poor conductivity and low transparency limit its development in the field of transparent supercapacitors. Summary of the Invention
[0004] The purpose of this invention is to provide composite electrode materials, preparation methods, and applications in transparent supercapacitors, which solve the problems existing in the prior art.
[0005] The present invention achieves the above objectives through the following technical solutions: The first objective of this invention is to provide a composite electrode material, which is composed of two-dimensional nanomaterials, a conductive polymer, and a transition metal oxide; the conductive polymer is filled between the layers of the two-dimensional nanomaterials, and the transition metal oxide is deposited on the surface of the two-dimensional nanomaterials and the conductive polymer; The two-dimensional nanomaterials are MXene and Ti3C2T. x -One of MXene, graphene, and reduced graphene oxide; The conductive polymer is one of poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), polyaniline (PANI), and polypyrrole (PPy); The transition metal oxide is one of manganese dioxide, nickel hydroxide, cobalt hydroxide, or nickel cobalt hydroxide.
[0006] As a further improvement of the present invention, the composite electrode material includes, but is not limited to, any one of the following: (1) The composite electrode material is Ti3C2T x -MXene / PEDOT:PSS / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PEDOT:PSS, and the transition metal oxide is MnO2; (2) The composite electrode material is rGO / PEDOT:PSS / MnO2, wherein the two-dimensional nanomaterial is reduced graphene oxide rGO, the conductive polymer is PEDOT:PSS, and the transition metal oxide is MnO2; (3) The composite electrode material is Ti3C2T x -MXene / PANI / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PANI, and the transition metal oxide is MnO2; (4) The composite electrode material is Ti3C2T x -MXene / PPy / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PPy, and the transition metal oxide is MnO2; (5) The composite electrode material is Ti3C2T x -MXene / PEDOT:PSS / NCOH, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, the conductive polymer is PPy, and the transition metal oxide is NCOH.
[0007] As a further improvement of the present invention, when manganese dioxide is used as the transition metal oxide in the composite electrode material, the manganese dioxide MnO2 has a nanosheet array structure with a vertical surface.
[0008] The second objective of this invention is to provide a method for preparing the above-mentioned composite electrode material, wherein a two-dimensional nanomaterial solution and a conductive polymer solution are mixed and spin-coated onto the surface of an ITO glass. After spin-coating, an annealing treatment is performed. Then, using the ITO glass containing the two-dimensional nanomaterial / conductive polymer as the working electrode, a transition metal oxide is grown on the glass surface by electrodeposition to obtain the two-dimensional nanomaterial / conductive polymer / transition metal oxide.
[0009] As a further improvement of the present invention, using Ti3C2T x Taking MXene / PEDOT:PSS / MnO2 as an example, the preparation method includes the following steps: (1) Using Ti3AlC2 as the precursor material, an etching and precipitation reaction was carried out using hydrochloric acid and lithium fluoride. After the reaction, Ti3C2T was obtained by washing, sonication, and centrifugation. x -MXene solution; (2) The Ti3C2T x -MXene solution and PEDOT:PSS solution were mixed and ultrasonically coated onto an ITO glass substrate using a spin-coating method; the surface with Ti3C2T x Using an ITO glass substrate made of MXene / PEDOT:PSS composite material as the working electrode, MnO2 electrodeposition was performed to obtain Ti3C2T. x -MXene / PEDOT:PSS / MnO2.
[0010] As a further improvement of the present invention, step (1) specifically includes the following: Add hydrochloric acid to a preheated reactor, add lithium fluoride to the reactor in small amounts several times, stir to dissolve, then add Ti3AlC2 to the reactor in small amounts several times, and keep warm and stir for 24-48 hours. After black sediment appears, deionized water is added and centrifuged. The bottom precipitate is collected and washed with dilute hydrochloric acid. The solution is mixed until it does not stick to the wall. The precipitate is collected by centrifugation. The washing and centrifugation are repeated until the pH of the supernatant is ≥6. The precipitate is then collected. The precipitate was added to deionized water and brought to a final volume. An inert gas was then introduced and the mixture was sealed. The mixture was then placed in an ice-water bath and sonicated. After centrifugation, the upper and middle layers of liquid were collected to obtain Ti3C2T. x -MXene solution.
[0011] As a further improvement of the present invention, step (2) specifically includes the following: Ti3C2T x MXene was mixed with PEDOT:PSS solution and sonicated. The sonicated mixture was then evenly dropped onto ITO glass and spin-coated. After spin coating, the ITO glass with the composite material on its surface is placed on a hot plate for annealing to obtain Ti3C2T. x -MXene / PEDOT:PSS composite electrode material; Ti3C2T x -MXene / PEDOT:PSS composite electrode material was electrodeposited in a three-electrode electrochemical workstation using manganese acetate solution as electrolyte to obtain Ti3C2T. x-MXene / PEDOT:PSS / MnO2 composite electrode material.
[0012] As a further improvement of the present invention, the Ti3C2T x The mass ratio of MXene to PEDOT:PSS is 0.5:1-3:1.
[0013] As a further improvement of the present invention, the spin coating speed is 2600-3000 rpm and the spin coating time is 30-40 s; The annealing process is carried out at a temperature of 110-130℃ for 2-4 hours. The electrodeposition voltage is 0.3-0.6V, and the electrodeposition time is 10-60s.
[0014] A third objective of this invention is to provide the application of the above-mentioned composite electrode material in the electrodes of a transparent supercapacitor.
[0015] The beneficial effects of this invention are as follows: (1) The Ti3C2T proposed in this invention x -MXene / PEDOT:PSS / MnO2 composite material. MnO2, a pseudocapacitive material, can store energy through rapid and reversible redox reactions on and near the material surface, thus exhibiting high specific capacitance. However, due to its low intrinsic carrier (electron or hole) concentration and lack of continuous electron transport channels in its crystal structure, it suffers from poor conductivity. Among them, Ti3C2T... x MXene, as a novel two-dimensional sheet carbide, possesses high conductivity and stability. The introduction of the conductive polymer PEDOT:PSS reduces the stacking of MXene sheets, providing an effective pathway for ion transport and diffusion. Therefore, Ti3C2T... x -MXene / PEDOT: PSS combined with MnO2 can form stable conductive channels on the surface of the composite material, thereby enhancing the conductivity of the material.
[0016] (2) The Ti3C2T proposed in this invention x -MXene / PEDOT:PSS / MnO2 composite material, spin-coated Ti3C2T on ITO x -MXene / PEDOT:PSS can change the hydrophilicity of the substrate. On this basis, electrodeposition of MnO2 can make the composite material adhere more strongly to ITO. This further solves the problem of easy detachment of MnO2 from ITO, and makes the composite material have high stability.
[0017] (3) The Ti3C2T proposed in this invention x-MXene / PEDOT:PSS / MnO2 composite material, Ti3C2T x -MXene nanosheets and PEDOT:PSS form a uniformly dispersed composite structure through non-covalent bonds (such as hydrogen bonds and electrostatic interactions), avoiding the formation of Ti3C2T x -MXene's transmittance decreases due to aggregation, therefore Ti3C2T x The MXene / PEDOT:PSS composite material exhibits high transparency. However, manganese dioxide itself suffers from low transparency. In this invention, MnO2 is electrodeposited using a potentiostatic method (CP) on an electrochemical workstation and a three-electrode system. This method results in a vertical array morphology of MnO2 growth on ITO, ensuring that visible light can pass through the pores, thus giving the composite material high transparency.
[0018] (4) The Ti3C2T proposed in this invention x -MXene / PEDOT:PSS / MnO2 composite material. MnO2, due to its high specific surface area and porous structure, facilitates rapid ion diffusion and surface reactions, thus exhibiting high energy storage performance. To address the poor conductivity and stability of MnO2, Ti3C2T is introduced... x -MXene / PEDOT:PSS enables Ti3C2T x The MXene / PEDOT:PSS / MnO2 composite material exhibits high conductivity and stability, while the electrodeposition method of MnO2 allows the composite electrode to maintain high transparency. The electrode prepared by this invention achieves a combination of transparency and energy storage performance, and can be further extended to the application of other electrode materials in the fabrication of electrodes for transparent supercapacitors.
[0019] (5) The Ti3C2T proposed in this invention x In the MXene / PEDOT:PSS / MnO2 composite material, Ti3C2T x -MXene is replaced by reduced graphene oxide (rGO) to form rGO / PEDOT:PSS / MnO2 composite materials, and PEDOT:PSS is replaced by polyaniline (PANI) or polypyrrole (PPy) to form Ti3C2T x -MXene / PANI / MnO2 or Ti3C2T x -MXene / PPy / MnO2 composite material, where MnO2 is replaced by nickel cobalt hydroxide (NCOH) to form Ti3C2T x The MXene / PEDOT:PSS / NCOH composite material provides a new approach for the fabrication of electrodes using other electrode materials in transparent supercapacitors. Attached Figure Description
[0020] Figure 1 Ti3C2T prepared in this invention x Flowchart of the preparation process of MXene / PEDOT:PSS / MnO2 composite material; Figure 2 The Ti3C2T prepared in this invention x - MXene material surface ( Figure 2 a) Ti3C2T x - Cross-section of MXene material ( Figure 2 b), Ti3C2T x -MXene / PEDOT:PSS material ( Figure 2 c), Ti3C2T x -MXene / PEDOT:PSS / MnO2 material ( Figure 2 d) SEM images; Figure 3 The Ti3C2T in this invention x Transparency curves of MXene / PEDOT:PSS / MnO2 measured by a UV-Vis-NIR spectrometer in the wavelength range of 400-800 nm; Figure 4 Ti3C2T in this invention x -MXene / PEDOT:PSS / MnO2 materials were used at 5mV s -1 10mV s -1 20mVs -1 50mV s -1 100mV s -1 200mV s -1 Cyclic voltammetry curves at scan rate ( Figure 4 a) and respectively at 10 μA / cm 2 20μA / cm 2 50μA / cm 2 100μA / cm 2 200μA / cm 2 Constant current charge-discharge curves at current density ( Figure 4 b).
[0021] Figure 5 From left to right: Ti3C2T x -MXene / PEDOT:PSS / MnO2、Ti3C2T x -MXene / PANI / MnO2, rGO / PEDOT:PSS / MnO2, Ti3C2T x -MXene / PEDOT:PSS / NCOH digital photographs; Figure 6 Ti3C2T in this invention x -MXene / PANI / MnO2, rGO / PEDOT:PSS / MnO2, Ti3C2T x Transparency curves of MXene / PEDOT:PSS / NCOH measured by a UV-Vis-NIR spectrometer in the wavelength range of 400-800 nm; Figure 7 Ti3C2T in this invention x -MXene / PANI / MnO2, rGO / PEDOT:PSS / MnO2, Ti3C2T x -MXene / PEDOT:PSS / NCOH at 20mV s -1 Cyclic voltammetry curves at the scan rate. Detailed Implementation
[0022] The present application will now be described in further detail with reference to experiments and accompanying drawings. It should be noted that the specific embodiments described below are only for further illustration of the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above content.
[0023] 1. Explanation Unless otherwise specified, all methods used in this invention are conventional methods known to those skilled in the art, and all reagents and materials used are commercially available products, and all instruments used are conventional instruments known to those skilled in the art.
[0024] 2. Methods 2.1. Preparation of Ti3C2T x -MXene material like Figure 1 As shown, the preparation steps are as follows: (1) Place the reactor in a water bath and set the temperature to 50℃. Add 20mL of 12mol / L hydrochloric acid to the reactor. Weigh 1.6g of lithium fluoride and add it to the reactor in small amounts several times while turning on the magnetic stirrer. Stir for 10min to dissolve the lithium fluoride completely. Then, weigh 1.0g of Ti3AlC2 and add it to the reactor in small amounts several times. After it is completely added, stir at 50℃ for 24-48h. The mass ratio of Ti3AlC2, hydrochloric acid and lithium fluoride is 1:1.6:8.75. (2) After etching, deionized water was added to the black deposit after etching and centrifuged at 3500 r / min for 5 min. The bottom sediment was collected after one centrifugation. (3) Wash the precipitate with 1M dilute hydrochloric acid, and at the same time use a mixer to mix the solution so that it does not stick to the wall. Centrifuge 6-8 times (3500r / min, time 5min). (4) Add deionized water and continue centrifuging to collect the precipitate. The centrifugation speed is 3500-5000-8000-10000 r / min, 9-10 times, and each time is 5-10 min, until the pH of the last supernatant is ≥6. (5) Add the precipitate to deionized water, mix it in a mixer until it does not stick to the wall, transfer it to a special glass container, make up to 100 mL, purge with nitrogen for 5 min (or purge with argon to prevent oxidation), seal it, and sonicate for 2 h. At the same time, protect it with an ice-water bath to avoid irreversible damage to the material caused by the exothermic effect of the ultrasound. (6) After sonication, the obtained solution is centrifuged at 3500 r / min for 30 min. The middle and upper layer liquid is collected, which is the required Ti3C2T. x -MXene solution (Example 1).
[0025] 2.2. Preparation of Ti3C2T x -MXene / PEDOT:PSS composite material like Figure 1 As shown, the preparation steps are as follows: (1) Ti3C2T x Preparation of MXene / PEDOT:PSS mixed solution: Ti3C2T x MXene and PEDOT:PSS solution were mixed at a mass ratio of 0.5:1 to 3:1 and sonicated for 0.5 h. (2) Ti3C2T x Preparation of MXene / PEDOT:PSS composite electrode material: Place ITO glass on a benchtop spin coater, use a pipette to take 0.5 mL of the mixed solution from step (1) and drop it evenly onto the ITO glass, and set the spin coater speed to 2800 rpm, acceleration to 560 rpm / s, and time to 35 s for spin coating. (3) After spin coating, the ITO glass with the composite material on the surface is placed on a hot plate for annealing. The annealing temperature is 120℃ and the time is 3h to obtain Ti3C2T x -MXene / PEDOT:PSS composite electrode material (Example 2).
[0026] 2.3. Preparation of Ti3C2T x -MXene / PEDOT:PSS / MnO2 composite material like Figure 1 As shown, the preparation steps are as follows: To prepare a 0.1M manganese acetate electrolyte: Take 1.73g of anhydrous manganese acetate, add it to 100mL of deionized water, and sonicate it to dissolve. Ti3C2T x The MXene / PEDOT:PSS composite electrode material was electrodeposited in a three-electrode electrochemical workstation using manganese acetate solution as the electrolyte. The electrochemical workstation and the three-electrode system employed a potentiostatic method (CP) to electrodeposit MnO2, resulting in a surface with Ti3C2T... x Using an ITO glass substrate of MXene / PEDOT:PSS composite material as the working electrode, a platinum electrode with dimensions of 1cm × 1cm as the counter electrode, and a silver / silver chloride electrode as the reference electrode, the electrodeposition voltage was 0.5V and the electrodeposition time was 40s to obtain Ti3C2T. x -MXene / PEDOT:PSS / MnO2 composite material (Example 3).
[0027] 2.4. Performance Characterization See Figure 2 As shown, the Ti3C2T prepared in Example 1 was analyzed using scanning electron microscopy (SEM). x -MXene ( Figure 2 (ab), the Ti3C2T prepared in Example 2 x -MXene / PEDOT:PSS ( Figure 2 c) and the Ti3C2T prepared in Example 3 x -MXene / PEDOT:PSS / MnO2 ( Figure 2 d) Characterization was performed, and the results showed that Ti3C2T x -MXene material has a smooth and uniform surface and exhibits a layered stacked structure, Ti3C2T x -MXene / PEDOT:Ti3C2T in PSS material x -MXene nanosheets self-assemble into a planar structure, Ti3C2T x -MXene / PEDOT:PSS / MnO2 material shows MnO2 in Ti3C2T x -MXene / PEDOT:PSS matrix exhibits a vertical array growth pattern. Structurally, Ti3C2T x The surface lamellar structure of the MXene / PEDOT:PSS / MnO2 composite material provides a higher specific surface area and porosity, which is conducive to the rapid transport of electrons and ions into the material interior. At the same time, it can provide more redox active sites, which is beneficial to improving the electrochemical performance of the material.
[0028] See Figure 3As shown, the Ti3C2T prepared in Example 3 was analyzed using a UV-Vis-NIR spectrometer. x The transparency of the MXene / PEDOT:PSS / MnO2 composite material was tested, and the composite material achieved a high transparency of 83% at a wavelength of 550 nm.
[0029] See Figure 4 As shown, the Ti3C2T prepared in Example 3 was analyzed using an electrochemical workstation. x Cyclic voltammetry tests were conducted on the MXene / PEDOT:PSS / MnO2 composite material at different scan rates and constant current charge-discharge tests were performed at different current densities. The scan rate was increased from 5 mV / s... -1 Gradually rises to 200mV s -1 The area of the cyclic voltammetry curve increased significantly, but the shape of the curve remained almost unchanged, indicating that the material still exhibits excellent capacitive charge storage behavior and outstanding rate response during rapid ion and electron migration. Figure 4 The symmetrical triangle of the constant current charge-discharge (GCD) curve in b further confirms this. Calculations show that Ti3C2T x The MXene / PEDOT:PSS / MnO2 composite material exhibits excellent charge storage capacity at 20 mV s. -1 At the scan rate, the specific capacitance can reach 4.51 mF / cm. 2 .
[0030] This invention prepares Ti3C2T x -MXene / PEDOT:PSS / MnO2 composite material (such as...) Figure 5 This invention (based on the Zhejiang Provincial Department of Science and Technology) employs simple spin-coating and electrodeposition methods to achieve controllable synthesis of materials with well-defined compositions and structures. It fully utilizes the excellent charge storage capabilities of MnO2 and further optimizes its conductivity and transparency to obtain supercapacitor electrode materials with superior electrochemical performance. The electrode prepared by this invention combines transparency and energy storage performance and can be further extended to the application of other materials in the preparation of electrodes for transparent supercapacitors.
[0031] 2.5. Extension 2.5.1. Replacing Ti3C2T with other two-dimensional materials x -MXene Two-dimensional materials include, but are not limited to, MXene, graphene, and reduced graphene oxide. Reduced graphene oxide will be used in the following text.
[0032] 2.5.1.1. Preparation of reduced graphene oxide (rGO) materials (1) Weigh 2.5g of potassium persulfate and add 12ml of concentrated sulfuric acid, then add 2.5g of phosphorus pentoxide and dissolve with ultrasonic assistance for more than 10 minutes; (2) Take 3g of graphite powder, grind it thoroughly, add it to the mixed solution, and stir it in a water bath at 80℃ for more than 4.5h; (3) After cooling the solution to room temperature, dilute it with 500 ml of ultrapure water, stir for 10 min and let it stand for 12 h; (4) Slowly pour out the clear liquid above the solution, transfer the remaining substance to the vacuum filter and wash it 2-3 times with distilled water, and filter the residue and the remaining liquid together for 10 minutes. (5) Transfer the remaining solid to a beaker and seal it with aluminum foil. Then punch several ventilation holes in the aluminum foil and place the beaker in a vacuum drying oven at 60°C for more than 8 hours. (6) Take out the dried graphene oxide in the vacuum drying oven and add 120ml of concentrated sulfuric acid. Then take 15g of potassium permanganate and grind it in a mortar. After grinding, add the potassium permanganate to a beaker containing concentrated sulfuric acid and the medicine. During the addition process, control the temperature below 6 degrees. After the addition is completed, place the beaker in a water bath with a magnetic stirrer and heat it to 35 degrees and stir for 2 hours. (7) Use a dropper to add 250ml of deionized water into a beaker containing concentrated sulfuric acid and chemicals. During this process, keep the temperature of the solution in the beaker below 12 degrees Celsius. (8) After stirring with a magnetic stirrer at room temperature for 2 hours, add 700 ml of deionized water. After half an hour, turn off the magnetic stirrer and let the solution stand at room temperature overnight. (9) Take out the graphene oxide solution after standing, discard the supernatant and dilute it with 1000ml of deionized water and balance it. Then centrifuge it at 8000 rpm for 10 minutes. Next, dilute and balance the precipitate with 1 mol / L sulfuric acid and centrifuge it at 10000 rpm for 10 minutes. Then dilute and balance the precipitate with deionized water and centrifuge it at 10000 rpm for 10 minutes. After 10 minutes, discard the supernatant, dilute the precipitate with 1000ml of deionized water and stir it on a magnetic stirrer for 30 minutes to form the final graphene oxide solution.
[0033] (10) Take 105 mg of graphene oxide according to the concentration of the prepared graphene oxide solution and put it into a beaker, and add deionized water to dilute the graphene oxide solution to 600 mL. (11) Place the diluted graphene oxide solution into a 70°C water bath and add 360 mL of ammonia water. Heat at 80°C for 6 hours. After 6 hours, continue heating the water bath to 90°C and stir at 90°C for 1 hour to obtain the desired reduced graphene oxide suspension.
[0034] 2.5.1.2. Preparation of rGO / PEDOT:PSS composite material (1) Mix rGO and PEDOT:PSS solution at a mass ratio of 0.5:1-3:1 and perform ultrasonication for 0.5-2 h; (2) Preparation of rGO / PEDOT:PSS composite electrode material: Place ITO glass on a desktop spin coater, use a pipette to take 0.5 mL of the mixed solution obtained in step (1) and drop it uniformly onto the ITO glass, set the spin coater to a rotation speed of 2600-3000 rpm, an acceleration of 540-580 rpm / s, and a duration of 35-40 s, then perform spin coating; (3) After spin coating is completed, place the ITO glass with the composite material on its surface on a heating plate for annealing treatment, wherein the annealing temperature is 110-130°C and the annealing time is 2-4 h, so as to obtain the rGO / PEDOT:PSS composite electrode material; 2.5.1.3. Preparation of rGO / PEDOT:PSS / MnO₂ composite material Preparation of 0.1 M manganese acetate electrolyte: Weigh 1.73 g of anhydrous manganese acetate, add it into 100 mL of deionized water, and perform ultrasonication to dissolve it; Perform electrodeposition on the rGO / PEDOT:PSS composite electrode material in an electrochemical workstation with a three-electrode system using manganese acetate solution as the electrolyte. The electrochemical workstation and the three-electrode system perform electrodeposition of MnO₂ via the constant potential method (CP). The ITO glass substrate with rGO / PEDOT:PSS composite material on its surface is used as the working electrode, the counter electrode is a platinum electrode with a size of 1 cm×1 cm, and the reference electrode is a silver / silver chloride electrode. The electrodeposition voltage is 0.5-0.6 V and the electrodeposition time is 30-60 s, so as to obtain the rGO / PEDOT:PSS / MnO₂ composite material. The physical product is as shown by "nong" in Figure 5 above.
[0035] As shown in Figure 6 , a UV-Vis-NIR spectrometer is used to test the light transmittance of the rGO / PEDOT:PSS / MnO₂ composite material, and the light transmittance of the composite material at a wavelength of 550 nm is about 65%. Cyclic voltammetry tests at different scanning rates and galvanostatic charge-discharge tests at different current densities are performed on the rGO / PEDOT:PSS / MnO₂ composite material using an electrochemical workstation. The rGO / PEDOT:PSS / MnO₂ composite material also has excellent charge storage capacity. As shown in Figure 7 , at a scanning rate of 20 mV s -1 , the specific capacitance reaches 4.60 mF / cm 2 .
[0036] 2.5.2. Replace PEDOT:PSS with other conductive polymer materials The PEDOT:PSS used in this invention can be replaced by other conductive polymer materials (such as polyaniline (PANI) or polypyrrole (PPy)) to form Ti3C2T. x -MXene / PANI / MnO2 or Ti3C2T x -MXene / PPy / MnO2 composite material.
[0037] 2.5.2.1. Preparation of Ti3C2T x MXene material (1) Place the reactor in a water bath and set the temperature to 50℃. Add 20ml of 12mol hydrochloric acid to the reactor. Weigh 1.6g of lithium fluoride and add it to the reactor in small amounts several times while turning on the magnetic stirrer. Stir for 10min to allow the lithium fluoride to dissolve completely. Then, weigh 1.0g of Ti3AlC2 and add it to the reactor in small amounts several times. After the addition is complete, stir at 50℃ for 24-48h. (2) After etching, deionized water was added to the black deposit after etching and centrifuged at 3500 r / min for 5 min. The bottom sediment was collected after one centrifugation. (3) Wash the precipitate with 1M dilute hydrochloric acid, and at the same time use a mixer to mix the solution so that it does not stick to the wall. Centrifuge 6-8 times (3500r / min, time 5min). (4) Add deionized water and continue centrifuging to collect the precipitate. The centrifugation speed is 3500-5000-8000-10000 r / min, 9-10 times, and each time is 5-10 min, until the pH of the last supernatant is ≥6. (5) Add the precipitate to deionized water, mix it in a mixer until it does not stick to the wall, transfer it to a special glass container, make up to 100ml, purge with nitrogen for 5min (or purge with argon to prevent oxidation), seal it, and sonicate for 2h. At the same time, protect it with an ice-water bath to avoid irreversible damage to the material caused by the exothermic effect of the ultrasound. (6) After sonication, the obtained solution is centrifuged at 3500 r / min for 30 min. The middle and upper layer liquid is collected, which is the required Ti3C2T. x -MXene solution.
[0038] 2.5.2.2. Preparation of Ti3C2T x -MXene / PANI (or Ti3C2T) x -MXene / PPy composite material (1) Ti3C2T xMXene and PANI (or PPy) solution are mixed at a mass ratio of 0.5:1-3:1 and sonicated for 0.5-2h; (2) Place the ITO glass on a desktop spin coater, use a pipette to take 0.5 mL of the mixed solution obtained in step (1) and drop it uniformly on the ITO glass, set the rotation speed of the spin coater to 2600-3000 rpm, the acceleration to 540-580 rpm / s, and the time to 35-40 s, then perform spin coating; (3) After spin coating is completed, place the ITO glass with the composite material on the surface on a heating plate for annealing treatment, wherein the annealing temperature is 110-130°C and the annealing time is 2-4h, to obtain Ti3C2T x -MXene / PANI (or Ti3C2T x -MXene / PPy) composite electrode material; 2.5.2.3 Preparation of Ti3C2T x -MXene / PANI / MnO2 (or Ti3C2T x -MXene / PPy / MnO2) composite material Prepare 0.1 M manganese acetate electrolyte: weigh 1.73 g of anhydrous manganese acetate, add it into 100 mL of deionized water and sonicate to dissolve it; Place Ti3C2T x -MXene / PANI (or Ti3C2T x -MXene / PPy) composite electrode material is subjected to electrodeposition in a three-electrode system electrochemical workstation with manganese acetate solution as the electrolyte. The electrochemical workstation and the three-electrode system perform electrodeposition of MnO2 by the constant potential method (CP). The ITO glass substrate with Ti3C2T x -MXene / PANI (or Ti3C2T x -MXene / PPy) composite material on the surface is used as the working electrode, the counter electrode is a platinum electrode with a size of 1 cm×1 cm, the reference electrode is a silver / silver chloride electrode, the electrodeposition voltage is 0.5-0.6 V, and the electrodeposition time is 30-60 s, to obtain Ti3C2T x -MXene / PANI / MnO2 (or Ti3C2T x -MXene / PPy / MnO2) composite material, the physical product is as shown by "Jiang" in Figure 5 .
[0039] As shown in Figure 6 , a UV-Vis-NIR spectrometer is used to characterize Ti3C2T xTransparency test is performed on the -MXene / PANI / MnO₂ composite material, and the transmittance of the two composite materials at a wavelength of 550 nm is 71.5% respectively. An electrochemical workstation is used to test Ti₃C₂T x -MXene / PANI / MnO₂ composite material by cyclic voltammetry at different scanning rates and galvanostatic charge-discharge test at different current densities. As shown in Figure 7 , at 20 mV s -1 scanning rate, the specific capacitance of Ti₃C₂T x -MXene / PANI / MnO₂ composite material reaches 4.16 mF / cm 2 . PANI forms hydrogen bonds or chemical bonds with functional groups such as -OH and -O on the surface of MXene, which enhances charge transport, resulting in a higher specific capacitance.
[0040] 2.5.3. Replacement of MnO₂ with other pseudocapacitive materials The other pseudocapacitive materials are transition metal oxides, including but not limited to one of ruthenium oxide, manganese dioxide, nickel oxide, and nickel-cobalt hydroxide. The following is the preparation of Ti₃C₂T x -MXene / PEDOT:PSS / NCOH composite material.
[0041] (1) Preparation of Ti₃C₂T x -MXene and Ti₃C₂T x -MXene / PEDOT:PSS are the same as above.
[0042] (2) 3 mmol / L nickel sulfate hexahydrate (NiSO₄⋅6H₂O), 5 mmol / L cobalt sulfate heptahydrate (CoSO₄⋅7H₂O) and 3 mmol / L thiourea (CH₄N₂S) are dissolved in 20 mL deionized water and stirred at room temperature for 10 min to obtain a precursor solution for NiCo-LDH electrodeposition.
[0043] (3) The Ti₃C₂Tₓ -MXene / PEDOT:PSS composite electrode material is electrodeposited in a three-electrode system electrochemical workstation with the NiCo-LDH precursor solution as the electrolyte. The electrochemical workstation and the three-electrode system perform electrodeposition of NCOH by the constant potential method (CP). An ITO glass substrate with Ti₃C₂Tₓ -MXene / PEDOT:PSS composite material on the surface is used as the working electrode, the counter electrode is a platinum electrode with a size of 1 cm×1 cm, the reference electrode is a silver / silver chloride electrode, the electrodeposition voltage is 0.5-0.6 V, and the electrodeposition time is 30-60 s, to obtain Ti₃C₂T x -MXene / PEDOT:PSS / NCOH composite material, the physical product is as shown in "lin" in Figure 5
[0044] like Figure 6 As shown, the Ti3C2T was analyzed using an ultraviolet-visible-near-infrared spectrometer. x Transparency testing was performed on the MXene / PEDOT:PSS / NCOH composite material, which showed a transparency of up to 85% at a wavelength of 550 nm. Electrochemical workstations were used to analyze the Ti3C2T... x The MXene / PEDOT:PSS / NCOH composite material was subjected to cyclic voltammetry at different scan rates and constant current charge-discharge tests at different current densities. Ti3C2T x -MXene / PEDOT:PSS / NCOH composites also exhibit excellent charge storage capabilities, such as Figure 7 As shown, at 20mV s -1 At the scan rate, the specific capacitance reaches 1.75 mF / cm. 2 .
[0045] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.
Claims
1. A composite electrode material, characterized in that, The composite electrode material is composed of two-dimensional nanomaterials, conductive polymers, and transition metal oxides. The conductive polymers fill the spaces between the two-dimensional nanomaterials, and the transition metal oxides are deposited on the surfaces of the two-dimensional nanomaterials and the conductive polymers. The two-dimensional nanomaterial solution and the conductive polymer solution are mixed and spin-coated onto the surface of ITO glass. After spin-coating, the glass is annealed. Then, using the ITO glass with two-dimensional nanomaterials / conductive polymers as the working electrode, transition metal oxides are grown on the glass surface by electrodeposition to obtain a composite electrode material containing two-dimensional nanomaterials / conductive polymers / transition metal oxides. The two-dimensional nanomaterial is Ti3C2T. x -MXene, one of the reduced graphene oxides; The conductive polymer is one of PEDOT:PSS, polyaniline PANI, and polypyrrole PPy; The transition metal oxide is one of manganese dioxide, nickel hydroxide, cobalt hydroxide, and nickel cobalt hydroxide; The composite electrode material includes Ti3C2T x -MXene / PEDOT:PSS / MnO2, rGO / PEDOT:PSS / MnO2, Ti3C2T x -MXene / PANI / MnO2、Ti3C2T x -MXene / PPy / MnO2、Ti3C2T x - Any one of MXene / PEDOT: PSS / NCOH; The composite electrode material has a transparency of 65%-85% at a wavelength of 550nm.
2. The composite electrode material according to claim 1, characterized in that, In the composite electrode material: (1) The composite electrode material is Ti3C2T x -MXene / PEDOT:PSS / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PEDOT:PSS, and the transition metal oxide is MnO2; (2) The composite electrode material is rGO / PEDOT:PSS / MnO2, wherein the two-dimensional nanomaterial is reduced graphene oxide rGO, the conductive polymer is PEDOT:PSS, and the transition metal oxide is MnO2; (3) The composite electrode material is Ti3C2T x -MXene / PANI / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PANI, and the transition metal oxide is MnO2; (4) The composite electrode material is Ti3C2T x -MXene / PPy / MnO2, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, wherein the conductive polymer is PPy, and the transition metal oxide is MnO2; (5) The composite electrode material is Ti3C2T x -MXene / PEDOT:PSS / NCOH, wherein the two-dimensional nanomaterial is Ti3C2T x -MXene, the conductive polymer is PPy, and the transition metal oxide is NCOH.
3. The composite electrode material according to claim 1, characterized in that, When manganese dioxide is used as the transition metal oxide in the composite electrode material, the manganese dioxide (MnO2) has a vertical nanosheet array structure on the surface.
4. A method for preparing a composite electrode material as described in any one of claims 1-3, characterized in that, With Ti3C2T x Taking MXene / PEDOT:PSS / MnO2 as an example, the preparation method includes the following steps: (1) Using Ti3AlC2 as the precursor material, an etching and precipitation reaction was carried out using hydrochloric acid and lithium fluoride. After the reaction, Ti3C2T was obtained by washing, sonication, and centrifugation. x -MXene solution; (2) The Ti3C2T x -MXene solution and PEDOT:PSS solution were mixed and ultrasonically coated onto an ITO glass substrate using a spin-coating method; the surface with Ti3C2T x Using an ITO glass substrate made of MXene / PEDOT:PSS composite material as the working electrode, MnO2 electrodeposition was performed to obtain Ti3C2T. x -MXene / PEDOT:PSS / MnO2.
5. The method for preparing the composite electrode material according to claim 4, characterized in that, Step (1) specifically includes the following: Add hydrochloric acid to a preheated reactor, add lithium fluoride to the reactor in small amounts several times, stir to dissolve, then add Ti3AlC2 to the reactor in small amounts several times, and keep warm and stir for 24-48 hours. After black sediment appears, deionized water is added and centrifuged. The bottom precipitate is collected and washed with dilute hydrochloric acid. The solution is mixed until it does not stick to the wall. The precipitate is collected by centrifugation. The washing and centrifugation are repeated until the pH of the supernatant is ≥6. The precipitate is then collected. The precipitate was added to deionized water and brought to a final volume. An inert gas was then introduced and the mixture was sealed. The mixture was then placed in an ice-water bath and sonicated. After centrifugation, the upper and middle layers of liquid were collected to obtain Ti3C2T. x -MXene solution.
6. The method for preparing the composite electrode material according to claim 4, characterized in that, Step (2) specifically includes the following: Ti3C2T x MXene was mixed with PEDOT:PSS solution and sonicated. The sonicated mixture was then evenly dropped onto ITO glass and spin-coated. After spin coating, the ITO glass with the composite material on its surface is placed on a hot plate for annealing to obtain Ti3C2T. x -MXene / PEDOT:PSS composite electrode material; Ti3C2T x -MXene / PEDOT:PSS composite electrode material was electrodeposited in a three-electrode electrochemical workstation using manganese acetate solution as electrolyte to obtain Ti3C2T. x -MXene / PEDOT:PSS / MnO2 composite electrode material.
7. The method for preparing the composite electrode material according to claim 6, characterized in that, The Ti3C2T x - The mass ratio of MXene to PEDOT:PSS is 0.5:1-3:1; The spin coating speed is 2600-3000 rpm, and the spin coating time is 30-40 s; The annealing process is carried out at a temperature of 110-130℃ for 2-4 hours.
8. The method for preparing the composite electrode material according to claim 6, characterized in that, The electrodeposition voltage is 0.3-0.6V, and the electrodeposition time is 10-60s.
9. The application of a composite electrode material as described in any one of claims 1-3 in a transparent supercapacitor.
Citation Information
Patent Citations
Polyaniline / graphene / nickel manganese hydroxide supercapacitor electrode material and preparation method thereof
CN108597890A
Lithium iron phosphate composite material and preparation method thereof
CN118579749A